Essays in spatial statistics - Valente, Fernanda Cristina (2023)
This thesis is composed by eight self-contained papers in spatial statistics. Five papers are applications of statistical decomposition for spatio-temporal analysis of changes in climate-related events. The sixth paper is an application of statistical decomposition for climatic time series to analyze the existence of changes in rainfall and temperature patterns. The two final papers deal with statistical decomposition for spatio-temporal analysis of coronavirus disease in the national and global scales.